Combined Klippel-Feil syndrome, Sprengel deformity, and diffuse large B-cell lymphoma: A rare case report - Golnaz Lotfian, MD; Amirmasoud Negarestani, MD; Sarah Gondek, BS; Aleksandr Raskind, DO; William Chen, MD; Emad Allam, MD (Radiology Case Reports)
Klippel-Feil syndrome (KFS) is a rare congenital disorder characterized by the fusion of cervical vertebrae, with a clinical presentation that can vary widely due to genetic and phenotypic diversity. While KFS can occur as an isolated anomaly, it is often associated with other congenital conditions, such as Sprengel deformity, which may present with or without an omovertebral bone, complicating diagnosis and management. This particular case also involves diffuse large B-cell lymphoma (DLBCL), the most common subtype of non-Hodgkin lymphoma. We hereby present a complex case of a 60-year-old male with the co-occurrence of KFS, Sprengel deformity, and DLBCL. Diagnostic imaging revealed an ill-defined right neck mass on ultrasound which was confirmed on neck CT. The CT also demonstrated an elevated left scapula and a left omovertebral bone, indicative of Sprengel deformity. There was fusion of the C5 and C6 vertebrae consistent with KFS. A whole-body F-18 FDG PET scan demonstrated significant uptake in the neck mass, leading to a biopsy that confirmed DLBCL. This case highlights the importance of comprehensive medical and imaging evaluations in diagnosing and managing the complexities associated with these disorders. In particular, awareness of the potential co-existence of congenital abnormalities and aggressive malignancies is critical in such cases.